Property rights for empowering low-income women: Summary Paper from the International Conference on Sustainable Food Security For All By 2020 - Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2001)
According to the author, strengthening their property rights over a whole range of assets is one of the most direct ways to empower [low-income] women, to improve their whole families' welfare, and to enhance overall food security." She discusses what can be done to strengthen women's control over assets and makes three important recommendations for enhancing women's welfare."